Kontaminasi Staphylococcus aureus pada Telepon Seluler Mahasiswa Kedokteran: Tinjauan Praktik Higiene dan Penggunaan Antiseptik dalam Pencegahan Transmisi Bakteri - Ayu Suci Pratiwi; Erizka Rivani (Journal of Educational Innovation and Public Health, 2026)
Mobile phones are widely used in daily life and may serve as reservoirs of microorganisms because of their frequent contact with hands, faces, and environmental surfaces. Staphylococcus aureus is one of the most commonly isolated bacteria from mobile phone surfaces and has the potential to cause various infections in humans. This study aimed to determine the prevalence of Staphylococcus aureus contamination on mobile phones used by medical students and to review hygiene practices and antiseptic use in the prevention of bacterial transmission. This study employed a descriptive cross-sectional design. A total of 60 mobile phones belonging to medical students at a private university in Indonesia were included. Samples were collected using a swab technique from phone screen surfaces and cultured on Mannitol Salt Agar (MSA). Data regarding hygiene practices were collected using questionnaires and analyzed descriptively using frequency and percentage distributions. Of the 60 mobile phones examined, 43 samples (71.7%) demonstrated colony growth interpreted as Staphylococcus aureus, while 17 samples (28.3%) showed no bacterial growth. Contamination was more frequently observed on phones owned by male students (58.1%) than female students (41.9%). Most respondents reported washing their hands with soap and water (66.7%), using antiseptic soap and water (28.3%), and cleaning their phone screens daily (66.7%). However, only 11.7% reported using disinfectants to clean their mobile phone screens. The prevalence of Staphylococcus aureus contamination on medical students’ mobile phones was high, indicating that mobile phones may serve as reservoirs and potential transmission media for bacteria. Although most respondents reported adequate hygiene practices, the use of disinfectants for mobile phone cleaning remained limited. Routine cleaning with alcohol-based antiseptics may represent a simple and effective strategy to reduce bacterial contamination and transmission.